Programas informáticos y su relación con la gestión contable en colaboradores de estudios contables de la ciudad de Iquitos año 2023 - Chavez Flores, Christian Andrew (2023)
The computer programs are a fundamental pillar at present in the process that involves the accounting management for the generation of useful information that allows having a reasonable security of the economic data and contributes to the process of analysis and adequate decision making, the investigation formulated to measure the relationship between computer programs and accounting management from the perspective of 67 accounting study collaborators, with a relational non-experimental study design and an observational quantitative approach, using a 24-question questionnaire with a Cronbach statistical reliability of 0.905 identifying as main results that the accounting programs present significant positive characteristics in relation to their usefulness, security, qualities of the program and accounting reports in the majority of study participants, that accounting management presents significant positive characteristics in relation to processing, quality, analysis and decision-making process in the majority of the study participants, that there is a considerable positive relationship between the computer programs, the quality of the information and the analysis process, and that there is a medium positive relationship between the computer programs and the registration process and the decision-making process, concluding that there is a considerable positive relationship with a Spearman's Rho correlation coefficient of 0.633 between computer programs and accounting management with a statistical significance of 0.000.